PELATIHAN DAN PENDAMPINGAN AKUNTANSI UNTUK UMKM PANGKALAN GAS BEKASI - aswar, Khoirul; Julianto, Wisnu (Jurnal Pengabdian Bukit Pengharapan, 2024)
Financial reports, which contain accounting information, must be transparent and accountable for by all entities. The entity's performance is displayed in the financial report, which internal or external stakeholders can utilise to inform small-scale business decisions. Bekasi Petrol Station faces challenges with income and expenses in promoting MSMEs' good governance. The inability to provide transparent, accountable, integrated financial reports that could have an impact on the Bekasi petrol station business is a result of their financial issues, which are tied to the financial report preparation process. In order to help Gas Station members achieve good governance in their financial management, Community Service aims to maximise the program for their comprehension and training in financial reports. The process of mentoring and simulating accounting information systems, as well as training petrol stations on how to prepare financial reports in accordance with applicable accounting standards, is the service approach that is employed. As a result of this service, personnel of Gas Station are capable of understanding and preparing financial reports.